2003
DOI: 10.1016/s0736-0266(02)00155-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurohistological examination of the inferior glenohumeral ligament of the shoulder

Abstract: The neural histology of the anterior band of the inferior glenohumeral ligament (IGHL) was studied in 11 fresh shoulder specimen using a special silver impregnation technique. Between the collagen fibers small myelinated and unmyelinated dendrites could be detected. The appearance of neurovascular structures in the adjacent synovial layer clearly exceeded the typical supply to soft tissues. Analysing about 11,000 sections Ruffini mechanoreceptors that are known to be slow adapting were found on the humeral ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Vangsness et al (1995) report Pacini and Ruffini receptors in the middle, anterior and superior glenohumeral ligaments, as well as free nerve endings in the lower half of the labrum. Steinbeck et al (2003) report Ruffini receptors in the humeral insertion of the inferior ligament. Gohlke et al (1998) did not find receptors in the glenohumeral ligaments, but did find receptors in the periarticular loose connective tissue.…”
Section: Proprioceptionmentioning
confidence: 99%
“…Vangsness et al (1995) report Pacini and Ruffini receptors in the middle, anterior and superior glenohumeral ligaments, as well as free nerve endings in the lower half of the labrum. Steinbeck et al (2003) report Ruffini receptors in the humeral insertion of the inferior ligament. Gohlke et al (1998) did not find receptors in the glenohumeral ligaments, but did find receptors in the periarticular loose connective tissue.…”
Section: Proprioceptionmentioning
confidence: 99%
“…Three physical parameters were retrieved from each optical slice and interpolated to 200 slices for each microcapsule (Matlab 6.0): area of dendrites (in pixels), dendritic length (total length of dendrites connected to a node in pixels), dendrite number (number of dendrites connected to a node) [22][23][24]. A dendrite was defined as a one pixel thick open branch, while a node as the point of origin of dendrites.…”
Section: Imaging and Characterization Of Nano-fibres In Microcapsulementioning
confidence: 99%
“…9 In the shoulder, this hypothesis is supported by studies examining JPS, which have reported that subjects reproduce position accurately and consistently near the end of motion. [10][11][12][13] To our knowledge, however, this effect has not been studied in patients with shoulder stiffness. Previous investigations assessed JPS in one specific plane; we measured JPS and proprioceptive feedback in an unconstrained shoulder model.…”
mentioning
confidence: 96%